Enhancing Economic Cooperation: A Regional Arbitration Centre for ASEAN? - KOH, Pearlie (Institutional Knowledge at Singapore Management University, 2000)
Economic co-operation within ASEAN can be said to have seriously begun only at the beginning of the nineties. Prior to that, it was well known that, ASEAN as a co-operative grouping, had existed mainly with a political and strategic focus. It is with this focus that ASEAN managed to establish and maintain cohesiveness through the years despite the shaky beginnings of what has been described as a 'brittle alliance' borne of a common fear of communism. And it is with this focus that ASEAN, as a regional grouping, has generally been hailed as a success.